2019
DOI: 10.2147/ott.s212536
|View full text |Cite
|
Sign up to set email alerts
|

<p>A retrospective six-patient series of apatinib for the treatment of persistent or recurrent carcinoma of the cervix</p>

Abstract: Objective Although advances have been made in the clinical and therapeutic management of women with cervical cancer, the best treatment for patients with metastatic or recurrent cervical cancer is still undefined. Apatinib, a novel inhibitor of vascular endothelial growth factor receptor-2 tyrosine kinases, has been successful in treating various malignancies. This study was conducted to evaluate the efficacy and safety of apatinib in the treatment of recurrent cervical cancer. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 23 publications
(23 reference statements)
1
8
0
Order By: Relevance
“…Some recent research results show that apatinib has a certain effect on cervical cancer. In 2019, several studies reported the effect of single‐agent apatinib treatment after failure of first‐line treatment in recurrent or advanced cervical cancer 17,19–21 . In 2020, Guo et al 22 assessed the clinical efficacy and safety of apatinib combined with chemotherapy or concurrent chemo‐brachytherapy as first‐line treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some recent research results show that apatinib has a certain effect on cervical cancer. In 2019, several studies reported the effect of single‐agent apatinib treatment after failure of first‐line treatment in recurrent or advanced cervical cancer 17,19–21 . In 2020, Guo et al 22 assessed the clinical efficacy and safety of apatinib combined with chemotherapy or concurrent chemo‐brachytherapy as first‐line treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these biologic rationales, apatinib might affect the treatment of patients with cervical cancer. In the past year, some articles have reported that apatinib may be active in patients with recurrent and metastatic cervical cancer after failure of first‐line treatment 16–21 . However, fewer studies focus on finding which group of patients should be more beneficial from the treatment of apatinib.…”
Section: Introductionmentioning
confidence: 99%
“…Apatinib, an oral multi‐targeted tyrosine kinase inhibitor, with independent intellectual property rights in China, plays a major role in regulating tumour angiogenesis through the inhibition of vascular endothelial growth factor (VEGF) signalling pathway. The efficacy and safety of apatinib have been demonstrated in RCC, and a dosage of 500 mg daily was usually administered 12‐14 . Careful dose modification is required and allowed for patients with unacceptable toxicity or poor PS 15 .…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…Consistent administration of low‐dose drugs might prolong the treatment duration and minimize toxicity. Apatinib, an oral small‐molecule inhibitor of VEGFR‐2 tyrosine, has proven to be effective in the treatment of advanced cervical cancer with manageable toxicities 12‐14 . According to Xiao and colleagues, all patients with recurrent, metastatic cervical cancer having Karnofsky Performance Score ≥70 were treated with 500 mg of apatinib daily.…”
Section: Case Summarymentioning
confidence: 99%
See 1 more Smart Citation